If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -15 = 2p + 2 Reorder the terms: -15 + 3p = 2p + 2 Reorder the terms: -15 + 3p = 2 + 2p Solving -15 + 3p = 2 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. -15 + 3p + -2p = 2 + 2p + -2p Combine like terms: 3p + -2p = 1p -15 + 1p = 2 + 2p + -2p Combine like terms: 2p + -2p = 0 -15 + 1p = 2 + 0 -15 + 1p = 2 Add '15' to each side of the equation. -15 + 15 + 1p = 2 + 15 Combine like terms: -15 + 15 = 0 0 + 1p = 2 + 15 1p = 2 + 15 Combine like terms: 2 + 15 = 17 1p = 17 Divide each side by '1'. p = 17 Simplifying p = 17
| 192+48x=432 | | v^2-19v+14=0 | | 6(8-5i)-(8i)= | | 4(u+4)=-3u-47 | | 23=-7x-2x+5 | | 3(x-21)=4+2x | | 10(x+3)-(-8x-4)=x-5+3 | | -12=16x+7 | | 5n+3=3-1-2n | | 4=12+m | | (2x-6)=26 | | y=ax+cv | | 5(10v+12)=9v+6(10-6v) | | -16a^2+63a+4=0 | | 2+3x+6x=-25 | | 3-2x=x+10 | | 10(x*3)-(-8x-4)=x-5+3 | | 6p-2(p+6)=8 | | 2+3x+6x=48 | | 2(z+2)-2(2z+5)=18 | | -8=4(x-3) | | 122-(6x+7)=6(x+4)+x | | 8x+41=-9(x+3) | | 7x+1-6x=-4 | | -3=5/6x+4 | | 4x^2+3x-612=0 | | 4n+2(2n-1)=14 | | 7b-0.5=2b+4.5 | | 5n+2=42 | | 4-2x+6x=48 | | 9(w-7)=3+8w | | 4y=-12x-36 |